Situational Leadership, Organizational Support, and Self-Efficacy as Predictors of Teacher Work Motivation in Indonesian Junior High Schools - Muhammad Triyoso; Aslamiah Aslamiah; Sulistiyana Sulistiyana (Journal of Social Work and Science Education, 2026)
This study examines the direct and indirect effects of situational leadership and organizational support on junior high school teachers’ work motivation, with self-efficacy as a mediating variable. A quantitative correlational design with path analysis was employed. The sample comprised 128 teachers randomly selected from a population of 203 teachers in Kotabaru Regency, Indonesia. Data were collected using validated Likert-scale questionnaires (Cronbach’s α > 0.96 for all variables). Path analysis revealed that situational leadership (β = 0.315, p = 0.008) and organizational support (β = 0.377, p < 0.001) have significant direct effects on self-efficacy, which in turn significantly predicts work motivation (β = 0.376, p = 0.010). Self-efficacy partially mediates the relationships between both situational leadership and organizational support on work motivation. The model explained substantial variance in self-efficacy (R² = 0.68) and work motivation (R² = 0.71). These findings confirm that teacher work motivation is enhanced by adaptive school leadership, supportive organizational environments, and strengthened teacher self-belief. Practical implications include developing principal training programs in situational leadership and creating organizational support systems that foster teacher self-efficacy. Limitations include the cross-sectional design and single geographic setting; future research should employ longitudinal designs across diverse educational contexts.